Total Suspended Particulate (TSP) simulation using the gaussian dispersion model - Arbi, Yaumal; Nofriya, Nofriya; Fitrianti, Rahma; Putri, Widia (Universitas Negeri Padang, 2023)
Air pollution is one of the most dangerous and worrying. One of the causes of air pollution is dust or Total Suspended Particulate (TSP), namely particles with a diameter of <100 μm. The Total Suspended Particulate causes visual distrurbances and respiratory disorders such as URTI (Upper Respiratory Tract Infection). According to data from Badan Pusat Statistik Kota Padang in 2018, URTI represents the highest complaint in the district Lubuk Begalung as many as 5,534 cases (28%). In the district has industrial and transportation activities which are a source of air pollution. However, in there haven’t real time monitoring of air pollution, so it is necessary to carry out air pollution simulations. This study aims to determine the concentration of TSP ambient air pollution and to analyze the distribution air pollutant in the Lubuk Begalung District, Padang City. The research method used a quantitative, where the emission inventory and meteorological data used the Gauss dispersion model and surver 15 software. The maximum TSP from measurement and modeling results was 113.42 µg/m3 and 27.16 µg/m3. This result explain about the TSP concentration is still below the National BMUA in PP RI No. 41 of 1999, which is 230 µg/m3 (still in good condition). This is different from previous studies because this study only considers sources of industrial emissions without other sources of pollution. The result of the TSP distribution is moving increasingly towards the Southwest from the emission source and reaches a maximum concentration at the coordinate point (-0.98103 oS, 100.34567 oE), according to the dominant wind direction.